2019
DOI: 10.3389/fimmu.2019.01731
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Immune Responses During Thromboinflammation

Abstract: Besides mediating hemostatic functions, platelets are increasingly recognized as important players of inflammation. Data from experiments in mice and men revealed various intersection points between thrombosis, hemostasis, and inflammation, which are addressed and discussed in this review in detail. One such example is the intrinsic coagulation cascade that is initiated after platelet activation thereby further propagating and re-enforcing wound healing or thrombus formation but also contributing to the pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 165 publications
(225 reference statements)
1
104
0
4
Order By: Relevance
“…Following injury, restoration of vascular integrity, apoptosis, and recruitment of progenitor, stromal and immune cells are crucial for tissue restructuring, remodeling, and functionality. Platelets are involved in many of the stages of wound healing, and this is emphasized by the beneficial use of platelet‐rich plasma and platelet releasate in wound repair . They promote progenitor cell recruitment; promote cytokine, chemokine, proangiogenic, and growth factor release; and support fibrin generation and modulate immune and stromal cell recruitment and activation .…”
Section: Platelets Support Classical and Inflammatory Hemostasismentioning
confidence: 99%
“…Following injury, restoration of vascular integrity, apoptosis, and recruitment of progenitor, stromal and immune cells are crucial for tissue restructuring, remodeling, and functionality. Platelets are involved in many of the stages of wound healing, and this is emphasized by the beneficial use of platelet‐rich plasma and platelet releasate in wound repair . They promote progenitor cell recruitment; promote cytokine, chemokine, proangiogenic, and growth factor release; and support fibrin generation and modulate immune and stromal cell recruitment and activation .…”
Section: Platelets Support Classical and Inflammatory Hemostasismentioning
confidence: 99%
“…Therefore, we believe that platelets play an important role in severe acute lung injury after renal transplantation. Numerous studies have confirmed that platelets play not only a leading role in coagulation and thrombosis but also a key role in inflammation [36][37][38]. Platelets in the blood mainly exert anti-infection effects through the following mechanisms: ① After inflammatory stimulation, platelet Pselectin is transferred from the cytoplasm to the surface of the cell membrane, inducing adhesion of PMNs to endometrial cells and promoting the formation of neutrophil extracellular traps [39,40].…”
mentioning
confidence: 99%
“…Of major importance, glycoprotein (GP) Ib-IX-V, which binds VWF as well as P-selectin, Factors XI and XII, leukocyte integrin αMβ2, collagen, thrombin and kininogen, and GPVI, which binds collagen, fibrin and laminin (22), initiate platelet adhesion events. These receptors act in concert (23) to translate cues from the surrounding vascular environment to mediate molecular signaling pathways that lead to platelet activation, platelet adhesion as well as mediating interactions with other cells (24,25). The goal is for platelets to adhere and seal the damaged vessel area, thus maintaining hemostasis (26).…”
Section: Adheso-signaling Receptorsmentioning
confidence: 99%